The relationship between oxytocin, vasopressin and atrial natriuretic peptide levels and cognitive functions in patients with schizophrenia. Issue 4 (2nd October 2019) - Mutu Pek, Tugba; Yazici, Esra; Guzel, Derya; Kose, Elif; Yazıcı, Ahmet Bülent; Erol, Atila
ABSTRACT: Objective: The aim of this study was to investigate the relationship between oxytocin (OXT), vasopressin (AVP) and atrial natriuretic peptide (ANP) levels and cognitive functions in schzophrenia as well as to compare the findings to those in healthy controls. Method: Patients with chronic schizophrenia and ( n =63) healthy controls ( n =60) were evaluated with the Rey Auditory Verbal Learning Test (VLT), the Trail Making Test A-B (TMT), the Stroop Test, the Wechsler Memory Scale-Visual Production Subscale (WMS-V) and the Facial Emotion Recognition Tests. Blood samples were analysed by using ELISA. In the data analysis, the percentage distributions of the variables were obtained, the centrality and prevalence measures (mean, standard deviation) were calculated for the continuous variables, and the dependent and independent variables were evaluated using the chi-square test, the Student's t -test, and the Pearson correlation test. High score variables were determined by principal component analysis. For comparisons between groups; MANOVA applied. Results: Serum OXT, AVP and ANP levels did not differ between the groups. In the healthy control group, subscales of the Stroop, WMS-V and TMT-B tests showed better scores and correlated with levels of OXT ( p < .05). In the healthy controls, ANP levels and social cognition had a relationship with response times to happy facial expressions ( p < .05). The correlations of OXT, AVP and ANP with the social and cognitive parameters were different between the control group and the schizophrenia group ( p < .05). Conclusion: The different correlations in the healthy controls and schizophrenia group suggest deteriorations in the interactions and functions of hormones in patients and highlights the need for new investigations into different neurodegenerative illness samples.